THE EFFECT OF LEACHATE ON THE QUALITY OF SHALLOW GROUNDWATER IN THE FINAL WASTE DISPOSAL AREA OF SUWUNG KAUH VILLAGE, DENPASAR CITY - I Gusti Agung; Ayu Apty Anny; Riyani Bela; Azizah Aziz; Husnayaen; Adrian Pratama (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
Suwung Final Disposal Site (TPA) is a waste disposal site located in Suwung Kauh village, Denpasar District, south of the city of Denpasar, Bali. One of the problems arising from the accumulation of waste in the TPA is the presence of pollutants in the form of leachate. The aim of this research is to determine the level of concentration in the leachate and its effect on the quality of shallow groundwater around the Suwung landfill. Parameters tested on leachate include pH, chloride, turbidity, odor and color concentrations which will be compared with leachate water quality standards in the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.59/Menlhk/Setjen/Kum.1/7/2016 and shallow groundwater quality testing with the Regulation of the Minister of Health of the Republic of Indonesia 416/Menkes/PER/IX/1990.In the leachate water quality test, the results showed pH (7), chloride (3.0 mg/L), turbidity (194 FNU), odor and brownish black color (qualitative test using the five senses). Shallow groundwater quality tests are carried out in each well that has been determined. Testing the quality of shallow groundwater obtained results for the Suwung TPA monitoring well, pH (7), chloride (0.3mg/L), turbidity (1, 19FNU), odorless and colorless. Testing for residents' dug wells approximately 1 (one) kilometer away resulted in pH (6), chloride (1.5 mg/L), turbidity (1.95 FNU), odorless and colorless. Results from shallow groundwater characteristics testing shows that there are five parameters that meet water quality standards, namely pH, chloride, turbidity, odor and color.So it can be concluded that leachate water does not affectthe quality of shallow groundwater in residents dug wells around Suwung TPA with concentrations of pH,chloride,turbidity,odor and color